Entrepreneurial Spirit Dipengaruhi oleh Gaya Belajar Akomodator pada Pembelajaran Kewirausahaan - Eka Farida; Supriyanto Supriyanto (IKIP PGRI Bojonegoro, 2021)
The problem of educated unemployment has increased from year to year, this is due to the paradigm that the output of graduates from higher education is as a job seeker, so the application of accommodator learning styles in entrepreneurship learning is very relevant to solving these problems. The purpose of this study is to measure the accommodator learning styles of students in entrepreneurship learning and to examine the effect of accommodator learning styles on entrepreneurial learning on student entrepreneurial spirit. The research method used is experimental and ex-post facto explanatory. The population and sample in this study amounted to 35 respondents in the experimental class. Data analysis using qualitative descriptive analysis and t test. The results indicated that the learning style of the accommodator showed that the majority of students were classified as active experience, for the assessment of the student portfolio the results were very good and good. the application of the accommodator learning style was able to grow an entrepreneurial spirit by 55.3%. Permasalahan pengangguran terdidik mengalami kenaikan dari tahun ke tahun, hal ini disebabkan oleh paradigma bahwa output lulusan dari perguruan tinggi adalah sebagai seorang job seeker, sehingga penerapan gaya belajar akomodator pada pembelajaran kewirausahaan sangat relevan untuk memecahkan permasalahan tersebut. Tujuan penelitian ini yaitu untuk mengukur gaya belajar akomodator mahasiswa pada pembelajaran kewirausahaan dan menguji pengaruh gaya belajar akomodator pada pembelajaran kewirausahaan terhadap entrepreneurial spirit mahasiswa. Metode penelitian yang digunakan adalah eksperimen dan ex-post facto yang bersifat eksplanasi. Populasi dan sampel dalam penelitian ini berjumlah 35 responden pada kelas eksperimen. Analisis data menggunakan analisis deskriptif kualitatif dan uji t. Hasil penelitian mengindikasikan gaya belajar akomodator menunjukkan mayoritas mahasiswa tergolong dalam active experientation, untuk penilaian portofolio mahasiswa hasilnya nilai sangat baik dan baik. penerapan gaya belajar akomodator mampu menumbuhkan entreperenurial spirit sebesar 55,3%.